Ethnomathematical Exploration in Traditional Houses or Asmat Tribe as a Source of Mathematics Learning - s, Lisnawati; Kho, Ronaldo; Tandililing, Pitriana; Sirampun, Elsi; Ruamba, Marthinus Yohanes (Lembaga Penelitian dan Pendidikan Mandala, 2025)
This research is a qualitative study with an ethnographic approach. The purpose of this research is to analyze and describe the ethnomathematics activities, the mathematical elements found in the traditional Jew house of the Asmat tribe, and the mathematical elements in the Jew house that can be used as a source for mathematics learning. Data collection in this research was conducted through observation, interviews, and documentation. The instruments in this study are the research itself as the main instrument, along with supporting instruments in the form of interview guidelines and observation guidelines. Interviews were conducted with two informants, namely the Jew elders and the Asmat community, who are believed to have knowledge and understanding of how to build traditional houses and their components, as well as the meanings contained within these traditional houses. The research results show that there are ethnomathematics activities in the Jew traditional house, namely counting, locating, measuring, designing, and explaining. The mathematical elements found in the Jew traditional house are rectangles, triangles, cuboids and cubes, cylinders, arithmetic operations, area and volume, and distance. The results of this research can be used to develop mathematics learning tools.